Characterizing business rules for practical information systems - Carver, Andrew; Morgan, Tony (Springer Berlin Heidelberg, 2011)
The recognition of business rules as an important element of modern information systems has led to various proposals for business rule categorization schemes. In particular, a recent business rule standards proposal, the OMG standard for the Semantics of Business Vocabularies and Business Rules (SBVR) distinguishes between major categories of rule using a scheme derived from modal logic, based on alethic and deontic modalities. This paper examines some of the claims made for this categorization scheme in terms of the relationship with generally accepted logical systems, and identifies a number of problem areas. It further assesses the value of this modal logic classification scheme in the development and maintenance of information systems. Planned future work will look at an alternative scheme for practical categorization of business rules.